2007
DOI: 10.1021/jm070683u
|View full text |Cite
|
Sign up to set email alerts
|

From Docking False-Positive to Active Anti-HIV Agent

Abstract: Virtual screening of the Maybridge library of ca. 70,000 compounds was performed using a similarity filter, docking, and MM-GB/SA post-processing to seek potential non-nucleoside inhibitors of HIV-1 reverse transcriptase (NNRTIs). Though known NNRTIs were retrieved well, purchase and assaying of representative, top-scoring compounds from the library failed to yield any active anti-HIV agents. However, the highest-ranked library compound, oxadiazole 1, was pursued as a potential "near-miss" with the BOMB progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 34 publications
2
72
0
Order By: Relevance
“…A set of small substituents was reintroduced in place of each hydrogen; scoring with the BOMB program and FEP results led to synthesis and assaying of several polychloro analogues with EC 50 values as low as 310 nM in an HIV-infected T-cell assay. 5 The present report documents the FEP-guided developments that have now led to analogues of 2 with potencies in the 10-20 nM range. The essentially exhaustive FEP-guided lead optimization can serve as a model for future applications.…”
Section: Introductionmentioning
confidence: 81%
“…A set of small substituents was reintroduced in place of each hydrogen; scoring with the BOMB program and FEP results led to synthesis and assaying of several polychloro analogues with EC 50 values as low as 310 nM in an HIV-infected T-cell assay. 5 The present report documents the FEP-guided developments that have now led to analogues of 2 with potencies in the 10-20 nM range. The essentially exhaustive FEP-guided lead optimization can serve as a model for future applications.…”
Section: Introductionmentioning
confidence: 81%
“…Machicado and co-workers reported that prior to docking screening, the pre-selection of compounds was developed on the basis of volume and polarity characteristics [142], Barreiro and co-workers used a chemical similarity search [143,144], and Hu and co-workers discovered new Yersinia protein kinase A inhibitors by applying, prior to the docking studies, a machine-learning support vector machine model for obtaining a target-focused library beginning with a large chemical database [145].…”
Section: Other Docking-based Vs Methodsmentioning
confidence: 99%
“…Many successful VS results have been reported, and as suggested by Barreiro and co-workers, when the VS results seem to be second-rate, it is possible to use computational analyses to efficiently turn false positives into true active compounds [143,144].…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…Barreiro et al [48,101] docked a library of 70,000 commercially available compounds from the Maybridge catalog and 26 known NRRTIs into the HIV-1 RT binding site in order to identify potential leads. The docking program Glide 3.5, using its standard and extra-precision modes [102,103], narrowed down the search to the top 100 compounds which were postscored using an MM-GB/SA method.…”
Section: Hiv-1 Rtmentioning
confidence: 99%
“…FEP/MC guided optimization of a thiazole scaffold towards a low nM HIV-1 RT pyrimidine-based inhibitor [98][99][100]. FEP/MC guided optimization of an inactive oxadiazole scaffold towards a low nM HIV-1 RT inhibitor [48,70,101]. Transformation sequence used in the FEP simulations for the aryl 1-indanylketone-based compounds (2).…”
Section: Chemical Synthesismentioning
confidence: 99%